2022
DOI: 10.3389/fmicb.2022.900876
|View full text |Cite
|
Sign up to set email alerts
|

Fungi Occurrence in Ready-to-Eat Hazelnuts (Corylus avellana) From Different Boreal Hemisphere Areas

Abstract: The present study evaluated the fungal contamination of ready-to-eat dried hazelnuts considering for the first time the application of the same condition drying process of several hazelnut cultivars from different boreal hemisphere areas. Fifty lots of hazelnuts (Corylus avellana), belonging to eight cultivars from seven regions in four countries, were analyzed for fungal microbiota, describing both load levels and species diversity. For this purpose, a polyphasic approach consisting of morphological examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 77 publications
1
2
0
Order By: Relevance
“…A light microscope Leica DM500 was used for microscopic analysis in the laboratory of Agricultural University Plovdiv. In agreement with the description of Lombardi (Lombardi et al, 2022) the septate conidiophores, broom-like branched at the upper end were observed under the microscope. A chain of conidia forms on the branches.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…A light microscope Leica DM500 was used for microscopic analysis in the laboratory of Agricultural University Plovdiv. In agreement with the description of Lombardi (Lombardi et al, 2022) the septate conidiophores, broom-like branched at the upper end were observed under the microscope. A chain of conidia forms on the branches.…”
Section: Resultssupporting
confidence: 90%
“…Al, 2019. A comprehensive analysis on 134 isolates from hazelnut kernels revealed that the most widespread Penicillium species were P. commune (69 isolates), P. solitum (36 isolates) and P. expansum (29 isolates) (Lombardi et. al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis revealed that the largest number of co-occurring species occurred in ND samples and the highest number of species were common to the co-occurring species in other sample groups. Similarly, a previous study reported on the cooccurrence of different filamentous fungi, including Aspergillus and Penicillium, in hazelnuts (Corylus avellana) (Lombardi et al, 2022) and another study reported that Pseudopithomyces chartarum, Cladosporium allicinum, and Alternaria sect co-occurred together with Botrytis spp., P. digitatum, and P. glabrum in the indoor environment of homes in Denmark depending on moisture conditions (Andersen al., 2021). The newly identified in our study play a key role in the process of fruit decay in kiwifruit through their interactions.…”
Section: Discussionmentioning
confidence: 70%